2021
DOI: 10.1111/ele.13697
|View full text |Cite
|
Sign up to set email alerts
|

Letter: Trophic interactions regulate peatland carbon cycling

Abstract: Peatlands are the most efficient natural ecosystems for long‐term storage of atmospheric carbon. Our understanding of peatland carbon cycling is based entirely on bottom‐up controls regulated by low nutrient availability. Recent studies have shown that top‐down controls through predator‐prey dynamics can influence ecosystem function, yet this has not been evaluated in peatlands to date. Here, we used a combination of nutrient enrichment and trophic‐level manipulation to test the hypothesis that interactions be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 58 publications
(143 reference statements)
2
19
0
Order By: Relevance
“…While variable hydroperiods have been linked to accelerated carbon dioxide (CO 2 ) efflux from other temporary aquatic ecosystems via enhanced microbial decomposition (i.e., brown energy pathways; DelVecchia et al 2019), research from our study sites has shown that elevated algal production (green energy pathway) can offset increases in CO 2 efflux during periods of inundation (Kane et al 2021). Further, we have recently demonstrated that predatory macroinvertebrates can substantially reduce CO 2 emissions by limiting herbivore access to algal biomass, resulting in greater primary productivity and CO 2 uptake in peatlands (Wyatt et al 2021). Collectively, these findings suggest that the presence or absence of an algal-based food web has consequences for carbon cycling in temporary aquatic ecosystems.…”
Section: Discussionsupporting
confidence: 49%
“…While variable hydroperiods have been linked to accelerated carbon dioxide (CO 2 ) efflux from other temporary aquatic ecosystems via enhanced microbial decomposition (i.e., brown energy pathways; DelVecchia et al 2019), research from our study sites has shown that elevated algal production (green energy pathway) can offset increases in CO 2 efflux during periods of inundation (Kane et al 2021). Further, we have recently demonstrated that predatory macroinvertebrates can substantially reduce CO 2 emissions by limiting herbivore access to algal biomass, resulting in greater primary productivity and CO 2 uptake in peatlands (Wyatt et al 2021). Collectively, these findings suggest that the presence or absence of an algal-based food web has consequences for carbon cycling in temporary aquatic ecosystems.…”
Section: Discussionsupporting
confidence: 49%
“…Water-column concentrations of nitrate (NO 3 À ) and phosphate (PO 4 À ) are typically <23 and 5 µg Á L À1 , respectively, and pH ranges from 5.5 to 6.9 during the summer growing season (Rober et al 2014). A detailed description of the site's physical and chemical characteristics has been provided in Wyatt et al (2021). This fen has a top-down food web with three trophic levels (Ferguson et al 2021); algal biofilm, herbivores, and predatory macroinvertebrates (most of which are insect larvae).…”
Section: Methodsmentioning
confidence: 99%
“…In turn, predators of algal herbivores may cause cascading trophic effects on algal assemblage structure if they control the density or foraging activities of herbivores ( Alvarez andPeckarsky 2014, Gravem andMorgan 2019). By shaping the composition of this basal resource, animals have the potential to regulate aspects of ecosystem metabolism during periods of surface-water inundation in northern peatlands (e.g., Wyatt et al 2021).…”
mentioning
confidence: 99%
“…It is increasingly evident that biofilms regulate carbon fluxes in ecosystems, such as boreal peatlands and streams (Battin et al., 2016; Wyatt et al., 2021). In these ecosystems, the phototrophic community of biofilms ensures primary production, and their heterotrophic community ensures the decomposition and cycling of carbon and other nutrients (Bartrons et al., 2012; Battin et al., 2003; Besemer, 2015; Wu, 2017a).…”
Section: Importance Of Biofilms Growing On Non‐biological Interfacesmentioning
confidence: 99%
“…Biofilms provide the living environment for many primary consumers and are grazed by both invertebrates and vertebrates such as tadpoles (Füreder et al., 2003; Hecky & Hesslein, 1995; Rott et al., 2006). The trophic ecology of biofilms and their consumers is of particular interest given their relevance in carbon cycling: the absence of top‐down controls by animals against biofilm herbivory was shown to increase carbon dioxide emissions in boreal peatlands, highlighting the cascading effects of the loss of biodiversity (Wyatt et al., 2021). Particularly, boreal ecosystems are expected to experience changes in resource availability through climate change, shifting biofilm communities towards heterotrophy under certain conditions (Myers et al., 2021).…”
Section: Importance Of Biofilms Growing On Non‐biological Interfacesmentioning
confidence: 99%